Hepatoprotective activity of novel nutraceuticals of curculigo Orchioide root extract - Lalitha Chembet; N.Harikrishnan (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The aim of this study is to investigate hepatoprotective activity of hydroalcoholic extract of curculigo orchoide root in highly active antiretroviral administered rats. Animals were randomized and divided into five groups (I-V) of six animals in each group. Group I served as normal control and fed orally with normal saline 5ml/kg body weight daily for seven days. Group II rats as toxic control where as Group IV and V were treated with low dose and high doses with the Curculigo orchoide s respectively in controlled released formulation orally daily for seven days. Group III animals are treated with standard drug silymarin 25mg/kg(p.o) daily for seven days. On the seventh day, paracetamol suspension was given by oral route, in a dose of 750mg/kg body weight to all rats except the rats ingroup I .The biochemical parameters were estimated after an 18h fast following the last dose